Emerging Ideas: Matrix Metalloproteinase-2 in Muscle Atrophy - Liu, Xuhui (Springer-Verlag, 2010)
BACKGROUND: Muscle atrophy impacts almost every patient seen for orthopaedic conditions. Unfortunately, no effective treatment is available to date. Matrix metalloproteinases (MMPs), especially MMP-2, are involved in skeletal muscle atrophy. MMP-2 null mice reportedly have substantially reduced muscle atrophy after tendon transection compared with wild-type mice, suggesting MMP-2 plays an important role in muscle atrophy. Although the exact mechanisms remain unknown, a newly-discovered intracellular form of MMP-2 suggests a possible novel mechanism of MMP-2 digesting muscle matrix during muscle atrophy. I propose a new pharmacologic treatment for muscle atrophy using selective MMP-2 inhibitors. QUESTIONS/HYPOTHESIS: I hypothesize: (1) intracellular MMP-2 plays an important role during muscle atrophy by digesting intramuscular matrix; (2) AP-1 and NFAT signal transduction pathways are responsible for expression and activation of the intracellular MMP-2 during muscle atrophy; and (3) specific MMP-2 inhibitors can serve as a novel pharmacologic strategy in treating disuse-induced muscle atrophy. METHOD OF STUDY: Expression and activity of extracellular and intracellular MMP-2 will be determined in a mouse tendon transection model. The role of AP-1 and NFAT signal transduction pathways in MMP-2 transcriptional regulation in muscle atrophy will be determined using chromatin-immunoprecipitation (ChIP) and small interfering RNA (siRNA). I also will test the feasibility of treating muscle atrophy using selective MMP-2 inhibitors. SIGNIFICANCE: Understanding the signaling transduction pathway of extracellular and intracellular MMP-2 expression during muscle atrophy may lead to novel treatments for muscle atrophy that preserve the normal physiologic function of MMP-2.